Method for manufacturing unburned basic brick

The described method addresses the challenges of producing non-sintered basic bricks by forming magnesium silicate hydrate as a binder through the addition of water to a refractory raw material compound, resulting in enhanced strength and corrosion resistance across a broad temperature range.

JP2025054577APending Publication Date: 2025-04-08KROSAKI HARIMA CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023163694
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing methods for producing non-sintered basic bricks face challenges such as reduced strength between 400 and 1000°C, formation of low melting points, and potential dissolution of binder components into molten steel, leading to inadequate corrosion resistance and durability.

Method used

A method involving the addition of water to a refractory raw material compound containing fine magnesia and silica powders, followed by kneading, pressing, and heat treatment at temperatures between 60°C and 1000°C, to form magnesium silicate hydrate as a binder, thereby enhancing strength and corrosion resistance without low melting point issues.

Benefits of technology

The method effectively maintains strength and corrosion resistance of the unsintered basic bricks across a wide temperature range, preventing peeling and ensuring durability in applications like molten metal containers and cement rotary kilns.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025054577000001
    Figure 2025054577000001
Patent Text Reader

Abstract

To provide a method for manufacturing an unburned basic brick which does not have reduction of corrosion resistance by creation of a low melting point substance, is free from concern such as melting of binder component into molten steel and digestion of magnesia, and uses a binder with suppressed strength degradation at 400 to 1000°C.SOLUTION: Water is added to a refractory raw material compound that contains magnesia having the particle diameter of less than 75 μm by 0.2 mass% or more and 30 mass% or less and silica having the particle diameter of less than 75 μm by 0.3 mass% or more and 2.5 mass% or less, in which the balance contains magnesia having the particle diameter 75 μm or more, and contains at least one kind of spinel, alumina and titania, and the compound is kneaded, and heating treatment is performed at the temperature of 60°C or more and 1000°C or less after press molding.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing unburned basic bricks which are used as molten metal containers in the steel industry and the like, or as lining materials for cement rotary kilns, etc. [Background technology]

[0002] Magnesia-chrome bricks, which have high corrosion resistance, are often used as refractories for lining molten metal vessels and cement rotary kilns. However, these magnesia-chrome bricks contain Cr2O3, which may lead to harmful hexavalent chromium in the bricks after use, which is problematic from an environmental hygiene perspective. Therefore, bricks that do not contain Cr2O3, such as magnesia-alumina bricks, magnesia-spinel bricks, and magnesia-titania-alumina bricks, are also used, which are so-called chrome-free basic bricks. However, general chrome-free basic bricks have disadvantages such as CO2 emissions and increased costs because they are fired at high temperatures of over 1500°C. Therefore, a method for producing unfired basic bricks is being considered to solve this problem.

[0003] For example, Patent Document 1 discloses a method for producing unburned basic bricks made of magnesia-alumina, and Patent Document 2 discloses a method for producing unburned basic bricks made of magnesia-titania-alumina. These manufacturing methods disclose that inorganic binders such as phosphates, silicates, and alumina cement are used as binders, which facilitate ceramic bonding under high temperatures and result in a strong structure.

[0004] However, when using phosphate as a binder, it is necessary to use it as an alkali metal phosphate such as sodium phosphate in order to prevent a sudden reaction with magnesia, and since they form low melting point materials with magnesia, the corrosion resistance decreases and sufficient durability cannot be obtained. In addition, there is a concern about the dissolution of phosphorus components into molten steel, so the use of phosphate is not preferable. Even when used as a silicate, alkali metal silicates such as sodium silicate tend to generate low melting point materials and the corrosion resistance decreases. In addition, since it is an alkaline binder, the amount of hydroxyl groups supplied to magnesia increases, and magnesium hydroxide is formed, which makes it easier for the brick to be digested, and there is a risk of cracks occurring during long-term storage or use. In order to minimize these adverse effects, it is possible to reduce the amount of alkali metal phosphate or alkali metal silicate used. For example, in the manufacturing methods of Patent Document 1 and Patent Document 2, 0.3 parts by weight of phosphate is used, but there is a problem that sufficient strength cannot be obtained. There are also silicate binders that do not contain alkali, such as silica sol, but they have not been put to practical use because the strength when made into bricks is insufficient. If alumina cement is used, it reacts with the CaO component in the slag to produce a low melting point substance, which reduces corrosion resistance and makes it difficult to achieve sufficient durability.

[0005] Patent Document 3 discloses the use of an aqueous magnesium chloride solution as a binder for unburned magnesia-spinel basic bricks. However, this method has problems in that the binder components decompose in the temperature range of 400 to 1000°C, which can easily cause a decrease in strength and embrittlement of the structure. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 8-143356 [Patent Document 2] Japanese Patent Application Publication No. 8-310875 [Patent Document 3] Patent No. 4328053 Summary of the Invention [Problem to be solved by the invention]

[0007] The problem to be solved by the present invention is to provide a method for producing unfired basic bricks using a binder which is free from the deterioration of corrosion resistance due to the formation of low melting point substances, the dissolution of binder components in molten steel, the digestion of magnesia, and the like, and which suppresses the deterioration of strength at 400 to 1,000°C. [Means for solving the problem]

[0008] The gist of the present invention is as follows. 1. A method for producing unfired basic bricks, comprising the steps of adding water to a refractory raw material mixture containing 0.2% by mass to 30% by mass of magnesia with a particle size of less than 75 μm, 0.3% by mass to 2.5% by mass of silica with a particle size of less than 75 μm, and the remainder containing magnesia with a particle size of 75 μm or more and at least one of spinel, alumina and titania, kneading the mixture, press-molding the mixture, and then heat-treating the mixture at a temperature of 60°C to 1000°C. 2. 2. The method for producing an unburned basic brick according to claim 1, wherein light-burned magnesia is used as the magnesia having a particle size of less than 75 μm, and silica flour is used as the silica having a particle size of less than 75 μm. 3. 3. The method for producing an unburned basic brick according to claim 1 or 2, wherein the content of magnesia having a particle size of 75 μm or more contained in the remainder of the refractory raw material mixture is 50% by mass or more and 90% by mass or less in 100% by mass of the refractory raw material mixture. 4. 4. The method for producing an unburned basic brick according to claim 3, wherein the remainder of the refractory raw material mixture contains at least spinel, and the spinel content is 5% by mass or more and 40% by mass or less in 100% by mass of the refractory raw material mixture. 5. 4. The method for producing an unburned basic brick according to claim 3, wherein the remainder of the refractory raw material mixture contains at least alumina, and the alumina content is 1% by mass or more and 15% by mass or less in 100% by mass of the refractory raw material mixture. 6. 4. The method for producing an unburned basic brick according to claim 3, wherein the remainder of the refractory raw material mixture contains at least titania, and the content of titania in 100% by mass of the refractory raw material mixture is 1% by mass or more and 15% by mass or less. Effect of the Invention

[0009] In the manufacturing method of the present invention, magnesium silicate hydrate is formed as a binder, so that there is no decrease in corrosion resistance due to the generation of low melting point substances, there is no concern about the dissolution of binder components in molten steel or the digestion of magnesia, and the like, and an unburned basic brick can be obtained which exhibits little decrease in strength at 400 to 1000°C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present inventors have discovered that an unfired basic brick having sufficient strength and corrosion resistance can be obtained by adding water to a refractory raw material mixture containing fine magnesia powder and fine silica powder, kneading the mixture, press-molding the mixture, and then heat-treating the mixture at a temperature of 60°C or higher and 1000°C or lower. The mechanism is considered to be as follows. In other words, magnesia fine powder and silica fine powder form gel-like magnesium silicate hydrate in the presence of water, and therefore function as a binder in the brick matrix when heat-treated at 60°C or higher, as the moisture in the brick is reduced. Even if the temperature of the brick rises and the magnesium silicate hydrate is dehydrated, the strength is maintained because an amorphous magnesium silicate bond is formed, and when further heat is applied, the amorphous magnesium silicate becomes forsterite, so that the decrease in strength can be suppressed up to the operating temperature. This magnesium silicate bond is characterized by its high hot strength, particularly at 600-1000°C, and when used as a lining material for molten metal containers and cement rotary kilns, it is highly effective in suppressing peeling of the working surface caused by weakening of the brick structure.

[0011] In the present invention, magnesia fine powder is used as a magnesia component for producing magnesium silicate hydrate at a content of 0.2% by mass to 30% by mass in 100% by mass of the refractory raw material blend. The smaller the particle size of the magnesia fine powder, the easier it is to form a hydrate in the presence of water, so a specific particle size of less than 75 μmm is used. That is, in the present invention, the refractory raw material blend contains 0.2% by mass to 30% by mass of magnesia fine powder, which is magnesia with a particle size of less than 75 μm. If the content of magnesia fine powder is less than 0.2% by mass, the binding structure in the brick structure will be insufficient, resulting in low strength, and if it exceeds 30% by mass, there will be too much fine powder, which will reduce moldability and cause lamination and reduced corrosion resistance.

[0012] In the present invention, light-burned magnesia can also be used as the magnesia fine powder. Light-burned magnesia is obtained by firing magnesite, magnesium hydroxide, etc. at a relatively low temperature, for example, 1400°C or less, usually 1000 to 1400°C, and is generally called activated magnesia or calcined magnesia, with an average particle size of 1 μm or less. This light-burned magnesia has a large specific surface area and is highly active, so it is more easily dissolved in water than sintered magnesia or fused magnesia, and therefore the magnesium silicate bonds develop well in the brick structure, thereby increasing the strength of the brick. This light-burned magnesia can be used at a content of 0.2% by mass or more and 5% by mass or less in the refractory raw material mixture (100% by mass).

[0013] In the present invention, fine silica powder, which is silica having a particle size of less than 75 μm, is used as the silica component for producing magnesium silicate hydrate at a content of 0.3% to 2.5% by mass in 100% by mass of the refractory raw material blend. If the content of fine silica powder is less than 0.3% by mass, the binding strength of the brick structure becomes insufficient, and if it exceeds 2.5% by mass, the flux component in the brick structure increases, reducing corrosion resistance.

[0014] As the silica fine powder, silica flour, fused silica, silica sol, fine powder of silica stone, etc. Since silica sol is in liquid form, its content is converted to SiO2. In the present invention, the term "silica flour" refers to fine silica particles having an average particle size of 10 μm or less, and generally refers to silica fume, fumed silica, and white carbon. Silica fume is a by-product obtained by collecting exhaust gas generated during the refining process of ferrosilicon, metal silicon, electrofused zirconia, etc., and is relatively inexpensive to obtain. Fumed silica is produced by hydrolysis in a flame of oxygen and hydrogen using silicon tetrachloride and other silicon compounds as raw materials. White carbon is obtained by decomposing sodium silicate using an acid or alkali. These silica flours are easily dissolved in alkaline water in which magnesia fine powder is partially dissolved, so that magnesium silicate bonds develop well in the brick structure, and the strength of the brick can be increased.

[0015] The raw material composition other than the magnesia having a particle size of less than 75 μm and the silica having a particle size of less than 75 μm contained in the refractory raw material blend of the present invention, i.e., the raw material composition of the remainder of the refractory raw material blend, can be a general raw material composition such as conventional magnesia-spinel bricks, magnesia-alumina bricks, magnesia-titania-alumina bricks, etc. The content of each raw material described below refers to the percentage in 100% by mass of the refractory raw material blend. First, the content of magnesia having a particle size of 75 μm or more, which is an essential raw material in the remainder, can be 50% by mass or more and 90% by mass or less. On the other hand, the remainder contains at least one of spinel, alumina, and titania, and among them, spinel can be used at a content of 5% by mass or more and 40% by mass mainly for the purpose of improving spalling resistance. Alumina can be used at a content of 1% by mass or more and 15% by mass or less mainly for the purpose of improving spalling resistance. Titania can be used at a content of 1% by mass or more and 15% by mass or less mainly for the purpose of improving corrosion resistance. Note that the particle sizes of alumina and titania are preferably less than 0.1 mm in terms of enhancing the spalling resistance improving effect and the corrosion resistance improving effect, respectively.

[0016] Next, the types of raw materials will be described. As magnesia, one having an MgO content of 90% by mass or more can be used, and fused magnesia, sintered magnesia, etc. can be used. As spinel, one having an Al2O3 content of 60-90% by mass, an MgO content of 10-40% by mass, and a total content of Al2O3 and MgO of 95% by mass or more can be used. As alumina, one having an Al2O3 content of 90% by mass or more can be used, and for example, fused alumina, sintered alumina, calcined alumina, etc. can be used. As titania, one having a TiO2 content of 90% by mass or more can be used, and both natural and artificial products can be used. In the present invention, the refractory raw material blend may contain one or more of metal powder, silicon carbide, graphite, pitch, carbon black, zirconia, glass powder, zirconia, zircon and boron carbide as refractory raw materials other than the above-mentioned magnesia, spinel, alumina, titania, and silica having a particle size of less than 75 μm, in an amount of 5 mass% or less.

[0017] In the method for producing the unburned basic brick of the present invention, water is added to the above-mentioned refractory raw material mixture, the mixture is kneaded, and the mixture is press-molded and then heat-treated at a temperature of 60°C to 1000°C. Water may be added in an appropriate amount according to the raw material composition in order to generate magnesium silicate hydrate as a binder and to ensure the moldability of the clay, and specifically, it may be added at a ratio of 0.5% by mass to 8% by mass relative to 100% by mass of the refractory raw material mixture. In this case, organic solvents such as ethylene glycol and methanol that are compatible with water may be used in combination with water.

[0018] In the present invention, since magnesium silicate hydrate functions as a binder, unlike conventional unfired bricks, it is not necessary to contain an alkali metal phosphate and / or an alkali metal silicate as a binder, so they do not need to be used, but they can be used as supplementary materials. In this case, however, the total content is preferably 1 mass% or less, and more preferably less than 0.2 mass%. If the total content exceeds 1 mass%, there is a concern that the corrosion resistance or creep resistance will decrease. In addition, in the case of an alkali metal phosphate, there is a concern that the phosphoric acid component will dissolve into molten steel. Here, the alkali metal silicate is sodium silicate, potassium silicate, etc., and the alkali metal phosphate is sodium phosphate, potassium phosphate, etc. In the present invention, sufficient strength can be obtained basically without using other binders, but it is possible to use other binders in combination with the present invention, i.e., binders generally used for refractory bricks can also be used in combination with the present invention.

[0019] Here, the particle size in the present invention refers to the size of the sieve openings when the refractory raw material particles are sieved to separate them. For example, magnesia with a particle size of less than 75 μm means magnesia that passes through a sieve with openings of 75 μm, and magnesia with a particle size of 75 μm or more means magnesia that does not pass through a sieve with openings of 75 μm. The average particle size in the present invention refers to the volume average particle size corresponding to the median cumulative value (D50) of a cumulative curve measured with a laser diffraction / scattering type particle size distribution analyzer. EXAMPLES

[0020] Table 1 shows the compositions of the refractory raw material blends in the examples of the present invention and the comparative examples, and the evaluation results of the obtained bricks.

[0021] [Table 1]

[0022] Among the refractory raw materials, the magnesia used was fused magnesia and lightly burned magnesia with 98% MgO by mass, the spinel used was fused spinel with 22% MgO and 73% Al2O3 by mass, the alumina used was sintered alumina and calcined alumina with 98% Al2O3 by mass, and the titania used was rutile with 98% TiO2 by mass. In addition, the silica fine powder, which is silica with a particle size of less than 75 μm, was silica flower with 98% SiO2 component, silica stone fine powder with 98% SiO2 component, and silica sol with 40% SiO2 component. The content of silica sol shown in Table 1 is the SiO2 equivalent value as described above.

[0023] Water was added to the refractory raw material composition of each example shown in Table 1 in the addition ratio shown in Table 1, kneaded, and molded into a shape of 230 mm x 114 mm x 100 mm using an oil press, and then heat-treated at 250°C for 5 hours to produce unburned basic bricks. For Examples 2 to 5, bricks were produced by varying the heat treatment temperature. Samples for measuring physical properties were cut out from these bricks, and the bending strength at room temperature and at 600°C was measured, and the spalling resistance and corrosion resistance were evaluated.

[0024] The bending strength at room temperature was measured by three-point bending. Specifically, rectangular specimens of 20×20×80 mm were prepared and the bending strength was measured at a pressure rate of 1.65 kN / s. The hot bending strength at 600°C was measured by three-point bending for each example of bricks obtained at a heat treatment temperature of 250°C. Specifically, rectangular specimens of 20 x 20 x 80 mm were prepared and heated to 600°C in a preheating furnace, then transferred to a test furnace and held at 600°C for 20 minutes, and the bending strength was measured at a crosshead speed of 0.05 mm / s.

[0025] Spalling resistance was evaluated by a quenching spalling test. In the quenching spalling test, a cubic sample with a side length of 50 mm was placed in an electric furnace heated to 1400°C, and after 15 minutes it was removed and air-cooled, and this operation was repeated 15 times. The spalling resistance was evaluated as × (not good) if part of the sample had peeled off within the 15th time, △ (passable) if large cracks were observed visually after the 15th time, and ○ (good) if only small cracks were observed.

[0026] The corrosion resistance was evaluated by a rotational corrosion test. In the rotational corrosion test, the inner surface of a drum having a horizontal rotation axis was lined with a test brick, slag was charged and heated to erode the brick surface. The heat source was an oxygen-propane burner, the test temperature was 1700°C, and the slag composition was CaO: 30% by mass, SiO2: 30% by mass, Al2O3: 20% by mass, FeO+Fe2O3: 20% by mass. The discharge and charging of the slag was repeated 10 times every 30 minutes. After the test, the amount of corrosion (mm) was calculated from the difference in thickness (mm) before and after the test at the maximum corrosion part of each brick. Then, a corrosion index was calculated with the amount of corrosion (mm) of the brick of "Comparative Example 1" listed in Table 1 taken as 100. The smaller the corrosion index value, the better the corrosion resistance.

[0027] In Examples 1 to 7, the content of magnesia fine powder, which is magnesia with a particle size of less than 75 μm, is different, but the results are within the range of the present invention and are good. In addition, the results of Examples 2 to 5, in which the heat treatment conditions were changed, show that sufficient strength can be obtained even if the heat treatment temperature is changed. In contrast, Comparative Example 1, which does not contain magnesia fine powder, had low strength and insufficient corrosion resistance. Also, Comparative Example 2, which contains magnesia fine powder in an amount exceeding the upper limit of the present invention and contains too much fine powder, which deteriorates the filling of the raw material during molding, resulted in low strength and insufficient spalling resistance and corrosion resistance.

[0028] Examples 8 to 12 have different contents of silica fine powder, which is silica with a particle size of less than 75 μm, but are within the range of the present invention and show good results. In contrast, Comparative Example 3 does not contain silica fine powder, and has low strength and insufficient spalling resistance and corrosion resistance. In Comparative Example 4, the content of silica fine powder exceeds the upper limit of the present invention, and spalling resistance and corrosion resistance are reduced.

[0029] In Examples 13 and 14, the content of magnesia having a particle size of 75 μm or more is different, but the results are within the range of the present invention and are favorable. In Examples 15 to 17, the alumina content in the magnesia-titania-alumina material was different, but the results were good and within the range of the present invention. In Examples 18 to 20, the titania content in the magnesia-titania-alumina material was different, but the results were good and within the range of the present invention. In Examples 21 to 25, the contents of titania, alumina, and spinel were different, but were within the range of the present invention and gave good results. In Examples 26 and 27, sodium phosphate was used as a binder in combination, and the results were good within the scope of the present invention. In contrast, in Comparative Example 5, which does not contain silica fine powder and uses only sodium phosphate as a binder, the strength was low and the spalling resistance and corrosion resistance were insufficient.

Claims

1. A method for producing an unburned basic brick, comprising the steps of adding water to a refractory raw material mixture containing 0.2% by mass to 30% by mass of magnesia having a particle size of less than 75 μm, 0.3% by mass to 2.5% by mass of silica having a particle size of less than 75 μm, and the remainder containing magnesia having a particle size of 75 μm or more and at least one of spinel, alumina and titania, kneading the mixture, press-molding the mixture, and then heat-treating the mixture at a temperature of 60° C. to 1,000° C.

2. 2. The method for producing unburned basic bricks according to claim 1, wherein light-burned magnesia is used as the magnesia having a particle size of less than 75 μm, and silica flour is used as the silica having a particle size of less than 75 μm.

3. 3. The method for producing an unburned basic brick according to claim 1, wherein the content of magnesia having a particle size of 75 μm or more contained in the remainder of the refractory raw material mixture is 50% by mass or more and 90% by mass or less, based on 100% by mass of the refractory raw material mixture.

4. 4. The method for producing an unburned basic brick according to claim 3, wherein the remainder of the refractory raw material mixture contains at least a spinel, and the content of the spinel in 100% by mass of the refractory raw material mixture is 5% by mass or more and 40% by mass or less.

5. 4. The method for producing an unburned basic brick according to claim 3, wherein the remainder of the refractory raw material mixture contains at least alumina, and the content of alumina in 100% by mass of the refractory raw material mixture is 1% by mass or more and 15% by mass or less.

6. 4. The method for producing an unburned basic brick according to claim 3, wherein the remainder of the refractory raw material mixture contains at least titania, and the content of titania in 100% by mass of the refractory raw material mixture is 1% by mass or more and 15% by mass or less.

Citation Information

Patent Citations

  • Magnesia based non-fired brick

    JP1996143356A

  • Alumina superfine powder-mixing magnesia unburned refractory brick

    JP1996310875A

  • magnesia-spinel brick

    JP4328053B2